2020
DOI: 10.1139/cjss-2018-0161
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties, heavy metals, and metal-tolerant bacteria profiles of abandoned gold mine tailings in Krugersdorp, South Africa

Abstract: Mine tailings are a potential source of heavy metals (HM) that can be toxic to microbes, plants, and animals in aquatic and terrestrial ecosystems. Bacteria have evolved several mechanisms to tolerate the uptake of HM ions. This study aimed to assess the physicochemical properties, concentrations of selected HM and metalloids [arsenic (As), nickel (Ni), lead (Pb), zinc (Zn), cadmium (Cd), and cobalt (Co)], and isolate potential metal-tolerant bacteria present at three abandoned gold mining sites with a view of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 63 publications
0
18
1
Order By: Relevance
“…The preponderance of aromatics fractions of the TPH compared to their aliphatic counterparts could be as a result of weathering of the pollutant due to the combined effect of chemical and physical factors such as volatilization, photo-oxidation, chemical-oxidation, thus leaving behind the more recalcitrant aromatic fractions. The soil pH (6.09) recorded shows that the soil is slightly acidic which implies that the heavy metals present in the sample will be labile as heavy metal mobility increases under acidic conditions [16].…”
Section: Discussionmentioning
confidence: 99%
“…The preponderance of aromatics fractions of the TPH compared to their aliphatic counterparts could be as a result of weathering of the pollutant due to the combined effect of chemical and physical factors such as volatilization, photo-oxidation, chemical-oxidation, thus leaving behind the more recalcitrant aromatic fractions. The soil pH (6.09) recorded shows that the soil is slightly acidic which implies that the heavy metals present in the sample will be labile as heavy metal mobility increases under acidic conditions [16].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to high concentrations of metals is therefore likely to exert selective pressure on bacterial communities favoring the emergence of highly metal-tolerant acidophilic bacteria [62]. Indeed, several authors have reported that bacteria isolated from mining areas that are highly contaminated are shown to exhibit high tolerance to different metals [63,64].…”
Section: Microbiological Properties Of Mine Tailings and Runoff Watermentioning
confidence: 99%
“…High concentrations of heavy metals have been recorded in sediments within and outside the perimeter of a mining area in South Africa. Fashola et al [42] reported concentrations of As, Cd, Pb and Zn above the recommended levels by South African guidelines for soils and sediment qualities guidelines from abandoned gold mining sites. In the study of the spatial assessment of heavy metals contamination in household soils in rural Limpopo Province, South Africa, Kapwata et al [43] reported high concentration of Pb, Cd, As and mercury (Hg), exceeding the Canadian reference levels of these heavy metals in soils characterized by abandoned mines and artisan mining activities in Limpopo Province, South Africa.…”
Section: Introductionmentioning
confidence: 97%
“…In this study, the concentrations of As, Cd, Pb, and Zn within a 1 km radius of a gold mining environment in North-West Province, South Africa was studied. These heavy metals are some of the most toxic heavy metals highlighted by the World Health Organization, WHO, [54][55][56] and they have been associated with gold mining operations [42,[57][58][59]. This study is important because there is currently limited published literature about the concentration of these heavy metals from the gold mine located in the North-West Province of South Africa.…”
Section: Introductionmentioning
confidence: 99%